Advances and Current Clinical Applications of Anterior Segment Optical Coherence Tomography Angiography - Luo, Man; Li, Yiqing; Zhuo, Yehong (Frontiers in Medicine, 2021)
Optical coherence tomography angiography (OCTA) is the most relevant evolution based on optical coherence tomography (OCT). OCTA can present ocular vasculature, show detailed morphology for assessment, and quantify vessel parameters without intravenous dye agent. Research on the anterior segment OCTA (AS-OCTA) is only in its initial phase, and its advances in clinical diagnosis and treatment efficacy evaluations require a detailed comparison to traditional imaging methods. In this review of AS-OCTA, we summarize its technical features, imaging advances, current clinical applications in various eye diseases, as well as its limitations and potential future directions. AS-OCTA offers potential advantages in ophthalmic imaging, and with further development it could become a common tool in the near future.